MAKNA KESEPIAN: SEBUAH KAJIAN TENTANG PSIKOLOGIS DAN SPIRITUAL - Khasanatil Marwah TS, Malikatun (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
Loneliness is a multifaceted phenomenon that impacts various dimensions of an individual's life, spanning both the psychological and spiritual realms. The main goal of the study was to explore the phenomenon of loneliness through the lens of psychology and spirituality, with a particular emphasis on explaining the definitions of each, the factors that influence them, and the results produced. The approach adopted in this inquiry involves the implementation of bibliographic investigation and critical examination of related sources including literary criticism, academic papers, and periodical releases. The findings of this study reveal that the interpretation of loneliness from a psychological and spiritual perspective plays an important role in mental well-being, including susceptibility to conditions such as depression and anxiety, as well as the potential for harm to spiritual well-being. The link between the psychological and spiritual aspects of loneliness suggests that meeting spiritual needs can reduce feelings of loneliness and improve psychological well-being. Strong spiritual resources allow individuals to effectively manage loneliness and stress, acting as a source of solace and calmness. These results contribute significantly to a comprehensive understanding and intervention strategies to overcome loneliness